Corrigendum to: Human Footprint on Natural Systems: Missing Post-war Scenario in the Urban Context of Damascus - Laurini, Eleonora; Mousli, Kindah; Alayoubi, Sedrah (International Journal of Architectural Engineering Technology, 2025)
All regions in Syria have witnessed a decline in green spaces due to the spread of illegal logging operations and a decline in interest in agricultural wealth due to the Systems. Missing post-war Scenario in the Urban Context of Damascus,” the author would like to revise the Acknowledgement and Credits sections to better reflect the contributions of collaborating institutions. The revised sections are provided below: Acknowledgement [A]FA has been collaborating with the Faculty of Architecture of the University of Damascus and the Damascus-based Reparametrize Foundation as part of their ongoing project Recoding Post-War-Syria, Zamalka. Students have been selected from each institution to participate in the lab. Credits [APPLIED] FOREIGN AFFAIRS, IoA, University of Applied Arts Vienna / Reparametrize Studio These revisions do not affect the scientific content, results, or conclusions of the article. The author and the editorial team regret the omission and have now rectified the record.